Exponential Stability of Hopfield Neural Network Model with Non-Instantaneous Impulsive Effects - Rui Ma; Michal Fečkan; Jinrong Wang (Axioms, 2023)
We introduce a non-instantaneous impulsive Hopfield neural network model in this paper. Firstly, we prove the existence and uniqueness of an almost periodic solution of this model. Secondly, we prove that the solution of this model is exponentially stable. Finally, we give an example of this model.